PENERAPAN PASAL 28 AYAT (2) UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM MENANGGULANGI DELIK UJARAN KEBENCIAN DI INTERNET - Windisen Windisen; Ade Adhari (Legal Standing : Jurnal Ilmu Hukum, 2021)
Hate speech is an act that is prohibited by law, with the development of technology, information and communication, hate speech is also found on the internet. Regulations regarding hate speech offenses on the internet in Indonesia are formulated in Article 28 paragraph (2) of Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE). However, in its application, Article 28 paragraph (2) of the ITE Law is considered problematic and does not provide legal certainty. Therefore, the problem formulated, namely "How from Article 28 paragraph (2) of the ITE Law in Overcoming Hate Speech Offenses on the Internet". The method used is empirical juridical which is a type of sociological legal research and can be mentioned by field research, which examines the applicable legal provisions and what has occurred in people's lives. The results of this study are the application of Article 28 paragraph (2) of the ITE Law referring to the SKB of the ITE Law which this article is intended for the act of spreading information that causes hatred based on SARA, but does not include a submission of opinions that contains criticism or disagrees, if the perpetrator found guilty will be subject to criminal sanctions in the form of imprisonment and fines.